Climate Change: Insights from Hinduism - Lal, Vinay (Journal of the American Academy of Religion, 2015)
© The Author 2015. Published by Oxford University Press, on behalf of the American Academy of Religion. All rights reserved. For permissions, please e-mail: journals.permissionsoup.comA LARGER CRISIS THAN ANY THAT typically makes the evening news—a terrorist attack, a relentless war that claims civilian lives as “collateral damage,” the lengthening shadow of death cast by a fatal virus—engulfs us all, even those who are sheltered from the cruel afflictions to which a good portion of humankind is still subject, especially in the global South. Over the last few years, as the opening article in this roundtable by Todd LeVasseur so clearly sets out, a consensus has slowly been emerging among members of the scientific community that climate change is presently taking place at a rate which is unprecedented in comparison with the natural climate change cycles that have characterized our earth in the course of the last half a million...